COVID-19 mortality risk for older men and women - N. David Yanez; Noel S. Weiss; Jacques-André Romand; Miriam M. Treggiari (BMC, 2020)
Abstract Background Case-fatality from COVID-19 has been reported to be relatively high in patients age 65 years or older. We sought to determine the age-specific rates of COVID-19 mortality at the population level. Methods We obtained information regarding the total number of COVID-19 reported deaths for six consecutive weeks beginning at the 50th recorded death, among 16 countries that reported a relatively high number of COVID-19 cases as of April 12, 2020. We performed an ecological study to model COVID-19 mortality rates per week by age group (54 years or younger, 55-64 years, and 65 years or older) and sex using a Poisson mixed effects regression model. Results Over the six-week period of data, there were 178,568 COVID-19 deaths from a total population of approximately 2.4 billion people. Age and sex were associated with COVID-19 mortality. Compared with individuals ages 54 years or younger, the incident rate ratio (IRR) was 8.1, indicating that the mortality rate of COVID-19 was 8.1 times higher (95%CI = 7.7, 8.5) among those 55 to 64 years, and more than 62 times higher (IRR = 62.1; 95%CI = 59.7, 64.7) among those ages 65 or older. Mortality rates from COVID-19 were 77% higher in men than in women (IRR = 1.77, 95%CI = 1.74, 1.79). Conclusions In the 16 countries examined, persons age 65 years or older had strikingly higher COVID-19 mortality rates compared to younger individuals, and men had a higher risk of COVID-19 death than women.